2020
DOI: 10.1055/s-0040-1714115
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Advanced Endoscopic Resection of Diverse Skull Base Malignancies: Technological Analysis during an 8-Year Single Institutional Experience

Abstract: Background Resection of skull base malignancies poses complex pathological and treatment-related morbidities. Recent technological advancements of endoscopic endonasal surgery (EES) offer the ability to reexamine traditional treatment paradigms with endoscopic procedures. The utility of EES was quantitatively examined in a longitudinal series with attention to morbidities and postoperative outcomes. Methods A single-center retrospective review was performed of all malignant sinonasal tumors from 2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Numerous studies have shown comparable outcomes between EEA and open approaches when adjusting for tumor type, stage, margins, and other prognostic factors 14,182,264,265,280–299 . Husain et al.…”
Section: Surgical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown comparable outcomes between EEA and open approaches when adjusting for tumor type, stage, margins, and other prognostic factors 14,182,264,265,280–299 . Husain et al.…”
Section: Surgical Approachmentioning
confidence: 99%
“…reviewed their 10‐year experience with EEA versus transcranial approach for skull base malignancies. This single‐institution retrospective review consisted of 30 open approaches versus 30 EEA 282 . There were no significant differences in age, sex, T stage, or Kadish stage between groups.…”
Section: Surgical Approachmentioning
confidence: 99%